A study of the factors influencing HIV-preventive intentions among “hookup” application users - Mengyu Li; Mengyu Li; Mengyu Li; Ning Li (Frontiers in Psychology, 2023)
“Hooking up” refers to the act of experiencing sexual intimacy with strangers without committing to a romantic relationship. Social media provide more convenient conditions for hooking up; however, it also poses a greater risk for HIV infection. Therefore, it is necessary to study the factors influencing the HIV-preventive intentions of those who engage in online dating to devise effective strategies for preventing the spread of HIV. This study consisted of a questionnaire that was distributed to 520 users of the Hello Group application. The survey results revealed that structural equation modeling is a useful framework for understanding the risk of HIV transmission in casual hookup encounters. In addition, combining the health belief model with the theory of planned behavior can provide recommendations for enhancing HIV-preventive intentions among users of dating applications. The results showed that mindfulness, the Chinese cultural context, perceived benefits, and self-efficacy were the main predictors of users' HIV-preventive intentions when using online dating applications. Among the perceived HIV risks, only perceived barriers had a negative effect on users' HIV-preventive intentions. In addition, attitude, subjective norms, and behavior control served as mediating variables between independent variables and HIV-preventive intentions; however, the mediating effect of attitude on perceived benefits and intentions was not significant. According to our study, some users misunderstand the risks and make incorrect assessments of the cultural risks of hooking up. Therefore, it is necessary to pay attention to the research on the psychological tendencies of users and risk intervention when studying the concept of hooking up.